Analisis Program Pemberian Reward Studi Kasus Pada Karyawan PT Citra Inti Semesta - Suryana, Dede Tatang; Harry Nugraha (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
This study aims to determine and obtain objective data and information regarding the analysis of the reward program case study on employees of PT Citra Inti Universe.This research uses a qualitative method with a descriptive type of analysis. The type used is a case study. Sata collection techniques are carried out using observation, interview, documentation, and triangulation methods. Informants were determined using purposive sampling technique with informants of HRD, technician leader, post sales staff, import purchasing, invoiching, engineering and sales. Based on the results of interviews and data analysis, the final results of this study state that PT Citra Inti Universe has done a good job of providing rewards in improving employee performance. Rewards given at PT Citra Inti Universe are salaries and bonuses, welfare, career development, promotions, and incentives. But in its implementation there are still obstacles such as in terms of promotion, having to choose the best employee from several existing employees. The solution is that PT Citra Inti Universe applies several provisions and regulations that must be obeyed by employees in order to attract the best employees who meet the criteria for getting the promotion,Keyword : Reward, Employee perfomance